Performance evaluation of a dynamic telepathology system (Panoptiq™) in the morphologic assessment of peripheral blood film abnormalities. (16th September 2014) - Goswami, R.; Pi, D.; Pal, J.; Cheng, K.; Hudoba De Badyn, M.
Summary Introduction The study evaluated the performance of a dynamic imaging telepathology system (Panoptiq™) as a diagnostic aid to the identification of peripheral blood film (PBF) abnormalities. Methods The study assumed a laboratory personnel working in a clinical laboratory were operating the telepathology system to seek diagnostic opinion from an external consulting hematopathologist. The study examined 100 blood films, encompassing 23 different hematological diseases, reactive or normal cases. Results The study revealed that with real‐time image transmission in live scanning mode of operation, the telepathology system was able to aid reviewers in achieving excellent accuracy, that is correct interpretation of morphologic abnormalities obtained in 83/84 of the hematologic diseases and 12/12 of the reactive/normal conditions (Sensitivity: 0.99; Specificity: 1.00). In contrast, when only saved static images in digital capture mode of operation were reviewed remotely, interpretative omissions occurred in 8/84 of the hematologic diseases and 0/12 of the reactive/normal conditions (Sensitivity: 0.91; Specificity: 1.00). It is hypothesized that real‐time operator‐reviewer communication during live scanning played an important role in the identification of key morphologic abnormalities for review. Conclusion Our study showed the Panoptiq system can be adopted reliably as a dynamic telepathology tool in aiding community laboratories in the triage of PBF cases for external diagnostic consultation.